2019
DOI: 10.5194/isprs-archives-xlii-3-w9-113-2019
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation of Total and Tropospheric Ozone Columns Over China

Abstract: Abstract. In this study, total ozone columns collected from nine sites of the AErosol RObotic NETwork (AERONET) in China are used to evaluate total ozone column monthly mean products of the Ozone Monitoring Instrument (OMI). The results show the correlated coefficient of the two datasets is 0.95. The long temporal variations and spatial distributions of the monthly mean products of the total ozone columns and tropospheric ozone columns in spring, summer, autumn and winter were plotted. The result shown in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
2
1
Order By: Relevance
“…At the height of 34 km, it can be seen that the ozone content in low latitudes (i.e., southeast and southwest China) is significantly higher than that in high latitudes (i.e., northeast and northwest China), with the maximum difference of 2.8 ppmv. This finding disagrees with Li et al (2019), which demonstrated that the total ozone content increases with the increase of latitude. The discrepancy can be explained by the fact that the results we present is only for the height of 34 km while the previous study is focused on the whole atmosphere.…”
Section: The Detection and Mapping Of The Changing Trend Of Ozonecontrasting
confidence: 95%
See 2 more Smart Citations
“…At the height of 34 km, it can be seen that the ozone content in low latitudes (i.e., southeast and southwest China) is significantly higher than that in high latitudes (i.e., northeast and northwest China), with the maximum difference of 2.8 ppmv. This finding disagrees with Li et al (2019), which demonstrated that the total ozone content increases with the increase of latitude. The discrepancy can be explained by the fact that the results we present is only for the height of 34 km while the previous study is focused on the whole atmosphere.…”
Section: The Detection and Mapping Of The Changing Trend Of Ozonecontrasting
confidence: 95%
“…The good performance of AIRS in the range from 800 hp to 250 hp and those less than 50 hp has also been confirmed by Wang et al (2019). Although AIRS present relatively large errors between 250 hp and 50 hp, it can capture the gradient and variability of ozone in the range from 250 hp to 50 hp well (Ma et al, 2019). Based on these studies, it is reasonable to consider that AIRS is able to capture the vertical gradient and variability of ozone in the stratosphere and middle and upper troposphere in China.…”
Section: The Evaluation Of Airs Dataset Based On In-situ Sitesmentioning
confidence: 65%
See 1 more Smart Citation